Sentence Structure: An Obstacle to Understanding English Poetry - เอี่ยมหฤท กฤศ; ศรีอุทัย จิรันธรา (Journal of Letters, 2018)
This research studies different types of sentence structures regarded as hindrances to an understanding of English poetry among Thai students, especially beginners, and suggests teaching activities to help reduce such problems. The sentence structures hypothesized to present obstacles are syntactic classes, pronoun references, inversion, coordination of noun phrases, verb phrases and adverb-like phrases, and phrasal and clausal modifiers as interrupting modifiers. The researchers designed questions to check the aforementioned grammar points, using three selected poems: Robert Frost’s “Out, Out –,” Henry Wadsworth Longfellow’s “The Cross of Snow,” and Dudley Randall’s “Ballad of Birmingham.” The subjects of the research were English-major sophomores. The findings show that these grammar points are not the sole factors impeding the understanding of English poems; there are other factors involved as well. Those factors are sentence length, the distance between the heads and the modifiers, and the insertion of other modifiers between a head and its modifier. The researchers also suggest before–between–after activities expected to enhance the understanding of English poetry among Thai students.